Dampak Aksesbilitas Pendidikan bagi Penyandang Tuli dengan Menggunakan Aplikasi “Soemeh” Berbasis Speech Recognition - Nurcholish Arifin Handoyono; Dinar Westri Andini; Trisharsiwi Trisharsiwi; Muhaimi Mughni Prayogo; Abdul Rahim; Zainur Wijayanto (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
In accordance with the mandate in the 1945 Constitution (amendment), every citizen has the right to education. This statement also applies to deaf people, where educational accessibility must be accommodated. The Soemeh application is here as an effort to provide educational accessibility for the deaf. This study aims to reveal the impact of using the Soemeh application on educational accessibility. This type of research uses a quantitative approach survey. The research population is the deaf disability community in Bandung, West Java. The sampling technique used a total quota of 20 respondents. Accessibility impact data was taken using a questionnaire instrument. The data analysis technique used descriptive quantitative. The results of the study indicate that the Soemeh application has a very high impact on educational accessibility for deaf people with the following details: (1) acceptance in the environment gets an average score of 3.35 including the very high category; (2) the ease of communication gets an average score of 3.35 including the very high category; (3) respect for deaf individuals gets an average score of 3.4 including the very high category; (4) future expectations to develop and achieve goals to get an average score of 3.5, including the very high category; (5) the achievement of independence gets an average score of 3.4 including the very high category; and (6) eliminating barriers and discrimination to get a score of 3.25 including the high category